Going Underground: An Experimental Archaeological Investigation of an Early Medieval Irish Souterrain - Tom Meharg (EXARC Journal, 2019)
During the summer of 2018 I completed a master’s degree in experimental archaeology and material culture at University College Dublin, this research was carried out for the final dissertation. The project was to build and test a 1:1 model of an early medieval Irish souterrain. The subterranean structure is based on one of over 3,500 examples of this feature identified in Ireland. The project allowed us to interact with the similar problems likely facing past societies in regards to design and engineering. Furthermore, by building such a feature we could engage with a souterrain as it may have existed in the early medieval period allowing interesting discussions on the experiential aspects of structure. The souterrain acted as an experimental space where I could investigate the food storage hypothesis by testing environmental conditions relating to the storage of certain foodstuffs. The results show that throughout the test period the model souterrain could maintain a constant internal temperature and humidity level most preferable for long term storage of some dairy products, root vegetables, and some fruits.